The incidence of common orthopaedic problems in newborn at Siriraj Hospital. - Chatupon Chotigavanichaya (2018)
The congenital orthopaedic anomalies in Thai population had a limited data and the previously studies are based on only hospital chart records. To determine the incidence of common congenital orthopedic problems by physical examination in newborn at Siriraj Hospital. A prospective study was conducted by physical examination of 3,396 newborns from June 2009 to September 2009. All orthopaedic abnormalities of newborns were recorded along with maternal age, obstetric history of mother, complications during pregnancy, complications in labour stage, mode of delivery and presentation. Sex of newborn, birth weight, body length and APGAR score were recorded. Incidence of calcaneovalgus was found in 60:1,000 live births following by metatarsus adductus in 7.6:1,000, polydactyly or syndactyly in 2.6:1,000, talipes equninovarus in 2.4:1,000, brachial plexus injury in 1.5:1,000, developmental dysplasia of hip in 0.6:1,000, osteogenesis imperfecta in 0.6:1,000, skeketal dysplasia in 0.6:1,000, congenital vertical talus in 0.3: 1,000 and fracture clavicle at birth in 0.3: 1,000. In the present study, the calcaneovalgus was the most common orthopaedic problem followed by metatasus adductus, polydactyly or syndactyly.